Hypothyroidism after craniospinal irradiation with proton or photon therapy in patients with medulloblastoma. (19th May 2018) - Bielamowicz, Kevin; Okcu, M. Fatih; Sonabend, Rona; Paulino, Arnold C.; Hilsenbeck, Susan G.; Dreyer, Zoann; Suzawa, Hilary; Bryant, Rosalind; Adesina, Adekunle; Dauser, Robert; Mahajan, Anita; Chintagumpala, Murali
Abstract: Background: Craniospinal irradiation (CSI) often results in endocrine deficiencies in children with medulloblastoma due to irradiation of the hypothalamic-pituitary axis (HPA) or the thyroid gland. CSI with Proton radiation therapy (PRT) has the potential to decrease the risk of hypothyroidism by reduction in radiation dose to these organs. This study compares the risk for hypothyroidism in patients with medulloblastoma treated with Photon radiation therapy (XRT) or PRT.Methods: The records of patients with medulloblastoma diagnosed at a single institution between 1997 and 2014 who received CSI were, retrospectively, reviewed. Ninety-five patients (54 XRT and 41 PRT) who had baseline and yearly follow-up thyroid studies were included. We used interval censored Cox regression to calculate hazard ratios of developing any, primary, and central hypothyroidism.Results: With a median time to last thyroid studies post radiation of 3.8 years in PRT and 9.6 years in XRT, 33/95 (34.7%) patients developed hypothyroidism (median time to hypothyroidism: 2.6 years). Hypothyroidism developed in 25/54 (46.3%) who received XRT vs. 8/41 (19%) in the PRT group (HR =1.85, p = .14). Primary hypothyroidism developed in 15/95 (15.8%) patients: 12/54 (22.2%) after XRT and 3/41 (7.3%) after PRT (HR =2.1, p = .27). Central hypothyroidism developed in 17/95 (18.0%) patients: 13/54 (24.0%) after XRT and 4/41 (9.8%) after PRT (HR =2.16, p = .18).Conclusions: The use of PRT in patients with medulloblastoma was associated with numerically lower but not significantly lower risk of hypothyroidism. Further studies including larger numbers and longer follow up must be performed to assess whether lower radiation doses achieved with PRT show statistically significant differences.